Предмет: Алгебра,
автор: isiididssi
Упростить выражение,досаточно легкое.
Приложения:
Ответы
Автор ответа:
0
Ответ:
Объяснение:
(√(4+√7) +√(4-√7) )² = (√(4+√7) )² + 2×√(4+√7) × √(4-√7) + (√(4-√7) )² =
=4 + √7 + 2×√(4+√7)×(4-√7) +4 - √7 = 8 + 2×√(4²-(√7)²) =
=8 + 2×√(16-7) = 8 + 2×√9 = 8 + 2×3 = 8 + 6 =14.
Похожие вопросы
Предмет: Русский язык,
автор: незнайка2003
Предмет: Английский язык,
автор: Алисаизсказки
Предмет: Русский язык,
автор: Aida2794
Предмет: Биология,
автор: dok20004
Предмет: Литература,
автор: Нинапомогите